2012
DOI: 10.1021/ic300129z
|View full text |Cite
|
Sign up to set email alerts
|

From a Cycloheptatrienylzirconium Allyl Complex to a Cycloheptatrienylzirconium Imidazolin-2-iminato “Pogo Stick” Complex with Imido-Type Reactivity

Abstract: The reaction of the cycloheptatrienylzirconium half-sandwich complex [(η(7)-C(7)H(7))ZrCl(tmeda)] (1) (tmeda = N,N,N',N'-tetramethylethylenediamine) with Li(Im(Dipp)N), generated from bis(2,6-diisopropylphenyl)imidazolin-2-imine (Im(Dipp)NH) with methyllithium, yields the imidazolin-2-iminato complex [(η(7)-C(7)H(7))Zr(Im(Dipp)N)(tmeda)] (2). The corresponding tmeda-free complex [(η(7)-C(7)H(7))Zr(Im(Dipp)N)] (5) can be synthesized via the 1,3-bis(trimethylsilyl)allyl complex [(η(7)-C(7)H(7))Zr{η(3)-C(3)H(3)(T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 133 publications
3
33
0
Order By: Relevance
“…The strongly exothermic formation of 1 nicely explains why coordination of THF occurs during the reaction of [(h 7 -C 7 H 7 )ZrCl(tmeda)] and K[C 3 H 3 (TMS) 2 ] in THF (Fig. 6) [11]. Although our experimental results have shown that PMe 3 cleanly replaces THF affording 2 (vide Scheme 3.…”
Section: Theoretical Studiessupporting
confidence: 57%
See 4 more Smart Citations
“…The strongly exothermic formation of 1 nicely explains why coordination of THF occurs during the reaction of [(h 7 -C 7 H 7 )ZrCl(tmeda)] and K[C 3 H 3 (TMS) 2 ] in THF (Fig. 6) [11]. Although our experimental results have shown that PMe 3 cleanly replaces THF affording 2 (vide Scheme 3.…”
Section: Theoretical Studiessupporting
confidence: 57%
“…Thus, weak binding can be concluded for the former, whereas comparatively strong bonds are generated for the latter. This is not only exemplified experimentally by the higher energy of activation for phosphine exchange (vide supra), but also by the observation that [(h 7 -C 7 H 7 )Zr(C 5 H 4 TMS)(thf)] readily loses THF under vacuum, although it was crystallized at low temperature [7a], while 1 is sufficiently stable [11].…”
Section: Theoretical Studiesmentioning
confidence: 99%
See 3 more Smart Citations